Exploring Racism in Health Pedagogy - Evans, Marian; Breny, Jean; Njoku, Anuli; Searcy, Yan (Race and Pedagogy Journal: Teaching and Learning for Justice, 2022)
Keywords: dept.pch

Implementation Tools, Program Staff, and Budgets - Valdez-Barkwell, CM; Breny, J; Fagan, M; Roe, K (Health Program Planning, Implementation, and Evaluation, 2022)
Keywords: dept.pch

Microbial Source Tracking in the Sasco Brook, Lower Farm River, and Goodwives River Watersheds of Long Island Sound - Brooks, Lauren; Caccone, Adalgisa; Cooper, Mark; Knauf, David; Pascucilla, Michael (Journal of Environmental Health, 2022)
Shortcomings in traditional methods for understanding sources of bacteriological contamination limit the ability of public health o cials to adequately protect public health and mitigate pollution sources. This study used polymerase chain reaction (PCR) as a tool for microbial source tracking to attempt to identify host species contributing bacteria to three watersheds fl owing into Long Island Sound. Samples were collected once a month near the mouth of each watershed and analyzed for other E. coli (a traditional fecal indicator) and genetic markers for members of the phylum Bacteroidetes. Genetic markers included host-specifi c markers that can be used to identify sources of contamination such as humans, domestic animals, and wildlife. Despite observing elevated E. coli levels in all three watersheds, we could not make a conclusive determination of actual sources using the available tools. Additionally, as there was disagreement between the E. coli levels and the presence of the general Bacteroidetes marker, it is important to evaluate the accuracy of this indicator with respect to recent fecal contamination and human health risks. Limitations posed by using indicator organisms, such as enterococci, illustrate the need to develop other methodologies for assessing actual sources of bacterial contamination.
Keywords: dept.pch; peer-reviewed; ⛔ No DOI found

Improving Water Quality in the Short Beach Neighborhood of Branford, Connecticut, 2019—A Citizen Science Project - Esenther, Sarah; Schlick, Katie; Jossart, Christopher; Wang, Ningjing; Dubrow, Robert; Pascucilla, Michael (American Journal of Public Health, 2022)
We initiated a collaboration between local government, academia, and citizen scientists to investigate high frequencies of elevated Escherichia coli bacteria levels in the coastal Short Beach neighborhood of Branford, Connecticut. Citizen scientist involvement enabled collection of short-duration postprecipitation outfall flow water samples (mean E. coli level = 4930 most probable number per 100 mL) and yielded insights into scientific collaboration with local residents. A records review and sanitary questionnaire identified aging properties with septic systems (3.3%) and holding tanks (0.6%) as potential sources of the E. coli contamination. (Am J Public Health. 2022;112(9):1261–1264. https://doi.org/10.2105/AJPH.2022.306943)
0 citations (Crossref) [2023-10-31]
Keywords: dept.pch; peer-reviewed

Undergraduate food insecurity, mental health, and substance use behaviors - Neal, Latasha; Zigmont, Victoria A. (Nutrition and Health, 2022)
Objective: Recent epidemiological research has found food insecurity to be a growing public health concern among college students. This study investigated food insecurity, mental health, and substance use behaviors among state university undergraduate students. Study Design: Cross-sectional survey. Methods: This was a secondary data analysis of the Student Health Survey. Undergraduate participants ( n = 589) completed the paper-based survey, which had an 84% response rate overall. Results: Approximately 38.5% of students were considered food insecure, 24.8% experiencing low food security, and 13.8% experiencing very low food security. Having a diagnosis of depression, experience of depressive symptoms, and marijuana use in the past 30 days were associated with food insecurity. Conclusion and Implications: Food insecurity is a serious health concern for college students. The results of this study indicate collocating food security and counseling services may enhance existing student resources to better support students facing food and nutrition insecurity, substance use, and depression.
3 citations (Crossref) [2023-10-31]
Keywords: SCSU-student; dept.pch; dept.psy

College students’ perceptions on safety measures and campus engagement during the COVID-19 pandemic - Risisky, Deb; Duff, Erin; Espinet, Jacqulynn (Journal of American College Health, 2022)
Objective: We examined students’ perceptions and opinions regarding others’ COVID-19 mitigation behaviors and how these behaviors impacted feelings of safety and desire for on-campus engagement. Participants: Undergraduate and graduate students enrolled at a midsize regional state university during the Spring 2021 semester (n = 893). Methods: A cross-sectional survey design was utilized with an online and anonymous questionnaire. Scale means were calculated followed by ANOVAs to determine significance. Results: Two independent variables impacted students’ feelings of safety for on-ground courses and activities: living situation (on campus, with roommates) and school year (freshman/sophomores). Underclassmen were more likely to desire in-person campus engagement. Conclusions: Students showed a willingness to return to campus, but also concern over peer behaviors and remaining safe. Returning to a pre-pandemic social environment is critical for students’ mental health, and making students feel safe on campus is an important first step to return campuses to vibrant educational and social communities.
2 citations (Crossref) [2023-10-31] _eprint: https://doi.org/10.1080/07448481.2022.2138717
Keywords: COVID-19; campus engagement; college students; dept.pch; mental health; peer-reviewed

The HPP Podcast: People, Places, Possibilities—Living & Reimagining Beyond the Page - Mata, Holly J.; Castle, Arden; Johnson, Chloe; Latz, Isabel; Castro, Justine Karla; Roe, Kathleen (Health Promotion Practice, 2022)
0 citations (Crossref) [2023-10-31]
Keywords: dept.pch; peer-reviewed

Captive Market Pricing and Lack of Transportation: A Survey of Undergraduate Food Insecurity at a Public University in New England - Zigmont, V.A.; Anziano, J.; Schwartz, E.; Gallup, P. (American Journal of Health Promotion, 2022)
Purpose: The purpose of this study is to describe the prevalence of food insecurity among college students and its relationship to on-campus food purchasing patterns and barriers to eating a healthy and sufficient diet, including the relative cost of food items on campus compared to national chain grocery stores. Design: A campus-wide survey using stratified sampling among undergraduates and food audit. Setting: An urban public university in New England. Subjects: A total of 951 surveys completed by undergraduates. Measures: Demographic characteristics, behavioral factors and food security status (measured using the USDA 6-item short form) were collected. Method: Descriptive and multivariable analyses were conducted to describe differences between food insecure and food secure undergraduates. Results: Overall, 35% of undergraduates experienced food insecurity in the past year (response rate = 92%). Food insecure undergraduates had different on-campus purchasing patterns than their food secure counterparts. Food insecure students were more likely to report barriers to healthy eating on all measures, including prices (AOR= 8.12, P <.0001), to experience housing insecurity (AOR= 2.64, P =.001) and to report that transportation is a barrier to buying groceries (AOR= 1.63, P =.01). After multivariable adjustment, food insecure undergraduates had higher odds of being African American (AOR= 1.57, P =.031) or other races (more than 1 race) (AOR= 3.35, P =.002) compared to white undergraduates. Conclusions: Food insecure college students face a variety of barriers to healthy eating on campus, including high food pricing on campus and limited transportation options. Further research is needed to inform campus resource development, policies and programming focused on food insecurity prevention for college students. © The Author(s) 2022.
4 citations (Crossref) [2023-10-31]
Keywords: college students; dept.pch; food insecurity; food prices; higher education; hunger; peer-reviewed; transportation

Barriers and facilitators to exclusive breastfeeding among Black mothers: A qualitative study utilizing a modified Barrier Analysis approach - Tran, Victoria; Reese Masterson, Amelia; Frieson, Tomeka; Douglass, Frankie; Pérez-Escamilla, Rafael; O'Connor Duffany, Kathleen (Maternal & Child Nutrition, 2022)
Breastfeeding has health benefits for both infants and mothers, yet Black mothers and infants are less likely to receive these benefits. Despite research showing no difference in breastfeeding intentions by race or ethnicity, inequities in breastfeeding rates persist, suggesting that Black mothers face unique barriers to meeting their breastfeeding intentions. The aim of this study is to identify barriers and facilitators that Black women perceive as important determinants of exclusively breastfeeding their children for at least 3 months after birth. Utilizing a Barrier Analysis approach, we conducted six focus group discussions, hearing from Black mothers who exclusively breastfed for 3 months and those who did not. Transcripts were coded starting with a priori parent codes based on theory-derived determinants mapped onto the Socioecological Model; themes were analysed for differences between groups. Facilitators found to be important specifically for women who exclusively breastfed for 3 months include self-efficacy, lactation support, appropriate lactation supplies, support of mothers and partners, prior knowledge of breastfeeding, strong intention before birth and perceptions of breastfeeding as money-saving. Barriers that arose more often among those who did not exclusively breastfeed for 3 months include inaccessible lactation support and supplies, difficulties with pumping, latching issues and perceptions of breastfeeding as time-consuming. Lack of access to and knowledge of breastfeeding laws and policies, as well as negative cultural norms or stigma, were important barriers across groups. This study supports the use of the Socioecological Model to design multicomponent interventions to increase exclusive breastfeeding outcomes for Black women.
3 citations (Crossref) [2023-10-31] _eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/mcn.13428
Keywords: barrier analysis; breastfeeding; dept.csc; dept.pch; focus group; peer-reviewed; public health; qualitative methods; social factors; sociocultural analyses

Comparing Environmental Policies to Reduce Pharmaceutical Pollution and Address Disparities - Desai, Meghana; Njoku, Anuli; Nimo-Sefah, Lillian (International Journal of Environmental Research and Public Health, 2022)
Pharmaceutical products, including active pharmaceutical ingredients and inactive ingredients such as packaging materials, have raised significant concerns due to their persistent input and potential threats to human and environmental health. Discourse on reducing pharmaceutical waste and subsequent pollution is often limited, as information about the toxicity of pharmaceuticals in humans is yet to be fully established. Nevertheless, there is growing awareness about ecotoxicity, and efforts to curb pharmaceutical pollution in the European Union (EU), United States (US), and Canada have emerged along with waste disposal and treatment procedures, as well as growing concerns about impacts on human and animal health, such as through antimicrobial resistance. Yet, the outcomes of such endeavors are often disparate and involve multiple agencies, organizations, and departments with little evidence of cooperation, collaboration, or oversight. Environmental health disparities occur when communities exposed to a combination of poor environmental quality and social inequities experience more sickness and disease than wealthier, less polluted communities. In this paper, we discuss pharmaceutical environmental pollution in the context of health disparities and examine policies across the US, EU, and Canada in minimizing environmental pollution.
6 citations (Crossref) [2023-10-31] Number: 14
Keywords: dept.pch; disparities; environmental policies; peer-reviewed; pharmaceutical pollution; pharmaceutical waste

Research engagement in a virtual world: Strategies for maintaining the power and impact of photovoice research online - Breny, J.M.; McMorrow, S.L. (Health promotion practice, 2022)
When our photovoice research intersected with the COVID-19 pandemic, we were thrust into a new world of adapting the method in the virtual environment. Between both authors, we had over two decades of experience implementing photovoice. However, that involved tried and true methods of working face to face and side by side with people in community-based settings. This article describes lessons learned from two virtual photovoice projects. One involved pivoting from a project already well underway in person to online and the other was designed for virtual implementation since that was the only option available. Key considerations discussed are navigating our institutional review boards, adapting project management, building community online, and sharing results and advocacy for social change. Dilemmas and key decisions in each of these areas are described for practitioners and community-based researchers who need or seek to transition their photovoice research to the virtual environment. Practical tips and strategies for implementation are described and offered to photovoice researchers.
3 citations (Crossref) [2023-10-31] tex.author_keywords: community-based participatory research (CBPR); health promotion; photovoice; qualitative methods; social justice tex.document_type: Article tex.pubmed_id: 35285320 tex.source: Scopus
Keywords: dept.pch; peer-reviewed

We are family: Effects of a relationship-strengthening prevention intervention on parenting behaviors among black and latino adolescent couples - Diaz, V.R.; Albritton, T.; Katague, M.; Dancy, V.; Breny, J.M.; Kershaw, T. (Journal of Family Issues, 2022)
Relationship strain or dissolution between new parents can affect the co-parenting relationship and parenting engagement. The purpose of this study was to evaluate the effect of a relationship-strengthening intervention on parenting behaviors among adolescent couples. Data from a pilot randomized control trial conducted with predominantly Black and Latino couples were analyzed using repeated measures analysis of variance. Observed intervention * time effects and intervention * time * gender effects were not statistically significant, but had small to moderate effect sizes. Intervention couples demonstrated increased parenting sense of competence compared to control couples. Gender differences in intervention effects were observed for both parenting experiences and parenting engagement. Given the pilot nature of the study, these findings provide preliminary evidence of the effectiveness of this couple-based intervention for improving parenting outcomes. Future research should assess the intervention in a larger sample and leverage technology-based approaches as methods for content delivery. © The Author(s) 2022.
0 citations (Crossref) [2023-10-31] tex.author_keywords: adolescents; Black and Latino parents; couple-based interventions; gender & family; parenting behaviors; romantic relationships tex.document_type: Article tex.source: Scopus
Keywords: dept.pch; peer-reviewed

Black women faculty and administrators navigating COVID-19, social unrest, and academia: Challenges and strategies - Njoku, A.; Evans, M. (International Journal of Environmental Research and Public Health, 2022)
Black women faculty and administrators in the United States are tackling a force of socioeconomic and racial disparities, emotional tolls and invisible burdens within academia, political turmoil, social unrest, and public health crises. COVID-19 has added an additional layer related to work responsibilities, the overall well-being of Black women faculty and administrators and the diverse students they encounter, and management of work and home responsibilities. This paper discusses perspectives and evidence-based strategies regarding Black women faculty and administrators who navigate academia and teach during times of COVID-19 and social unrest. We also outline strategies for university leaders to mitigate cultural and racial gaps in the classroom or workplace and foster diversity and inclusion in academia. © 2022 by the authors. Licensee MDPI, Basel, Switzerland.
15 citations (Crossref) [2023-10-31] tex.art_number: 2220 tex.author_keywords: Black women administrators; Black women faculty; Blacks/African Americans; COVID-19/coronavirus; Diversity; Equity; Health disparities; Higher education; Race/ethnicity; Racism tex.document_type: Article tex.pubmed_id: 35206408 tex.source: Scopus
Keywords: African American; African Americans; Article; COVID-19; Faculty; Female; Humans; Racism; SARS-CoV-2; United States; coronavirus disease 2019; dept.pch; epidemiology; evidence based practice; female; health care planning; health disparity; human; peer-reviewed; racism; social determinants of health; tertiary education; university

COVID-19 and Health Disparities: Opportunities for Public Health Curriculum Enhancement - Njoku, Anuli (COVID-19 and Higher Education in the Global Context, 2022)
COVID-19, the pandemic of highly contagious respiratory disease, presents a global public health emergency. The COVID-19 pandemic has increased awareness of the role of public health and its professionals in responding to the pandemic. Racial and ethnic minority groups in the United States are more likely to contract and die from COVID-19 versus Whites, highlighting health disparities. Higher education schools and programs in public health can help prepare students to address this global pandemic through expanded curriculum on social determinants of health disparities in COVID-19 outcomes, teachings on implicit bias and anti-racism, interprofessional education, and practice-based learning. Moreover, eliminating health disparities is a leading public health priority in the United States and can help attain the World Health Organization goal of achieving health equity. This chapter highlights the need for public health curriculum that outlines strategies to address racial and ethnic disparities in COVID-19 to prepare and motivate a future healthcare workforce. How to cite this chapter: Njoku, A. (2022). COVID-19 and health disparities opportunities for public health curriculum enhancement. In R. Ammigan, R. Y. Chan, & K. Bista, (eds), COVID-19 and higher education in the global context: Exploring contemporary issues and challenges (pp. 139-153). STAR Scholars. https://starscholars.org/product/covid-19-and-higed/
Keywords: dept.pch; ⛔ No DOI found